A Transcriptomic and reverse-engineering strategy reveals molecular signatures of arachidonic acid metabolism in 12 cancers - ARĞA, KAZIM YALÇIN (My University, 2023)
Cancer and arachidonic acid (AA) have important linkages. For example, AA metabolites regulate several critical biological functions associated with carcinogenesis: angiogenesis, apoptosis, and cancer invasion. However, little is known about the comparative changes in metabolite expression of the arachidonic acid pathway (AAP) in carcinogenesis. In this study, we examined transcriptome data from 12 cancers, such as breast invasive carcinoma, colon adenocarcinoma, lung adenocarcinoma, and prostate adenocarcinoma. We also report here a reverse-engineering strategy wherein we estimated metabolic signatures associated with AAP by (1) making deductive inferences through transcriptome-level data extraction, (2) remodeling AA metabolism, and (3) performing a comparative analysis of cancer types to determine the similarities and differences between different cancer types with respect to AA metabolic alterations. We identified 77 AAP gene signatures differentially expressed in cancers and 37 AAP metabolites associated with them. Importantly, the metabolite 15(S)-HETE was identified in almost all cancers, while arachidonate, 5-HETE, PGF2 alpha, 14,15-EET, 8,9-EET, 5,6-EET, and 20-HETE were discovered as other most regulated metabolites. This study shows that the 12 cancers studied herein, although in different branches of the AAP, have altered expression of AAP gene signatures. Going forward, AA related-cancer research generally, and the molecular signatures and their estimated metabolites reported herein specifically, hold broad promise for precision/personalized medicine in oncology as potential therapeutic and diagnostic targets.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Biotechnology; Molecular Biology and Genetics; Health Sciences; Natural Sciences; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; Life Sciences (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Genetik (klinik); Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Moleküler Tıp; Moleküler Biyoloji; Genetik; Genetics (clinical); Applied Microbiology and Biotechnology; Molecular Medicine; Molecular Biology; Genetics; arachidonic acid pathway; cancer; transcriptomic; drug repurposing; biomarkers; personalized medicine; COLORECTAL-CANCER; CELL-PROLIFERATION; EXPRESSION; CYCLOOXYGENASE-2; LIPOXYGENASES; PROSTAGLANDIN-F2-ALPHA; CARCINOMA; APOPTOSIS; SURVIVIN; INSIGHTS